Plasticity in Caste-Fate Determination During the Adult Stage in Temperate Polistes Wasps - Hideto Yoshimura; Ken Sasaki (Insects)
The reproductive division of labor is a fundamental characteristic of eusociality; thus, understanding the caste determination system underlying the reproductive division of labor would shed more light on the evolution of eusociality. In this review, we summarize the factors associated with caste determination in temperate Polistes paper wasps and focus on life histories associated with the loss or maintenance of caste plasticity during the adult stage among eusocial Hymenoptera. In many species of eusocial Hymenoptera, caste trajectories are differentiated by nutrition during the larval stages, indicating that caste plasticity is either absent or has not yet been confirmed. However, in temperate Polistes wasps, nutrition during the larval stage only causes biases in caste trajectory, with castes ultimately determined by environmental factors, such as day length and temperature, and colony conditions during the adult stage, indicating high caste plasticity during this stage. Therefore, morphological dimorphism and physiological differences between castes, such as in dopamine levels, have not been found in temperate Polistes wasps at emergence. This plasticity in temperate paper wasps could reflect the fact that females destined to be workers also have a chance to mate with males (especially early males) after emergence, leaving the possibility that they can produce daughters in the emerging year.